2004
DOI: 10.1111/j.1470-6431.2003.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Will consumers accept irradiated food products?

Abstract: This study examines consumers’ willingness to pay for irradiated beef products. About 58% of the respondents are willing to pay a premium for irradiated beef. An ordered probit with sample selection model was estimated. Standard errors of the marginal effects of the ordered probit model were estimated using the bootstrap method. Our findings suggest that females and those who think that improper handling contributes to food poisoning are more likely to pay a premium of 50 cents per pound for irradiated beef th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 8 publications
(19 reference statements)
0
25
1
1
Order By: Relevance
“…Nevertheless, when information about food irradiation-its nature and benefits to food safety and consumer health-is presented either in written form (leaflets, pamphlets, brochures, etc. ) or in audiovisuals, consumer anxiety tend to be reduced and the technology more favourably seen (Pohlman, Wood, & Mason, 1994;Resurreccion et al, 1995;Vickers & Wang, 2002;Oliveira & Sabato, 2004;Nayga, Poghosyan, & Nichols, 2004).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…Nevertheless, when information about food irradiation-its nature and benefits to food safety and consumer health-is presented either in written form (leaflets, pamphlets, brochures, etc. ) or in audiovisuals, consumer anxiety tend to be reduced and the technology more favourably seen (Pohlman, Wood, & Mason, 1994;Resurreccion et al, 1995;Vickers & Wang, 2002;Oliveira & Sabato, 2004;Nayga, Poghosyan, & Nichols, 2004).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…A positive response to irradiated foods can be enhanced if the consumer is allowed to compare irradiated and non-irradiated foods. Nayga et al (2004) reported that consumers would purchase irradiated foods and are "willing to pay premiums ranging from $0.05 to $0.50/b" depending on their level of concern and awareness and provision of sufficient background information. These finding demonstrate the importance of educating the public on the controversy, the technology, and the merits of irradiation.…”
Section: Consumer Attitude To Food Irradiationmentioning
confidence: 99%
“…For this reason, it is better to adequately inform people, avoiding opposite effects rather than changing the sentence with a softer one. Several studies (Cardello, Schutz, & Lesher, 2007;Farkas & Farkas, 2011;Fox, 2002;He et al, 2005aHe et al, , 2005bNayga, Poghosyan, & Nichols, 2004;Schutz, 1994;Schutz, Bruhn, & Diaz-Knauf, 1989) point out that an irradiated food label is perceived as a warning sign for the consumer, who tends to exclude the product in question and fails to pay a premium price for its purchase. However, a few studies conclude that consumers have a greater awareness of the processing treatment, which the product undergoes via the presentation of clear information stated on the label, contributing to increase the intention to purchase, as in the case of irradiated meat (Gallup, 1993;Rimal, McWatters, Hashim, & Fletcher, 2004), therefore rising the safetybased perception of the actual consumer (Schutz et al, 1989).…”
Section: European Labelling Obligations and The Issue Of The Iso 1447mentioning
confidence: 99%